The Influence of Family Ownership and Working Capital Strategy on Corporate Risk Taking and Its Impact on Corporate Innovation - Eunice Eunice; Dr Santi Yopie (Contemporary Journal on Business and Accounting, 2026)
Purpose – This study aims to examine the effect of family ownership and working capital strategy on corporate risk-taking and its impact on corporate innovation in family firms in Indonesia. Design/methodology/approach – This research employs a quantitative method using secondary data obtained from the financial statements of family firms in Indonesia. Data analysis is conducted to measure the relationships among family ownership, working capital strategy, corporate risk-taking, and corporate innovation. Findings – The results are expected to show that family ownership and working capital strategy have a significant effect on the level of corporate risk-taking. Furthermore, corporate risk-taking is predicted to have a positive impact on corporate innovation. These findings indicate that family firms with good working capital management and a long-term orientation tend to be more prepared to take strategic risks to foster innovation. Originality – This study provides an empirical contribution by integrating the roles of family ownership and working capital strategy into a single analytical framework to explain corporate risk-taking and its implications for corporate innovation. This research enriches the literature on family firm governance and financial management in the context of developing countries.